Lycopene and Its Antioxidant Role in the Prevention of Cardiovascular Diseases—A Critical Review. Issue 11 (17th August 2016) - Müller, Lars; Caris-Veyrat, Catherine; Lowe, Gordon; Böhm, Volker
Abstract : The present review is based mainly on papers published between 2000 and 2011 and gives information about the properties of the carotenoid lycopene in chemical and biological systems and its possible role in preventing cardiovascular diseases (CVD). The main aim of this report is to highlight its role as an antioxidant, also reported are bioactive properties that may influence the development of foam cells and protection against endothelial cell damage. The paper will also examine recent observations that lycopene may improve blood flow and reduce inflammatory responses. Lycopene possesses antioxidant properties in vitro, and some epidemiological studies have reported protective effects against the progression of CVD. The oxidation of human low density lipoproteins (LDL) is a fundamental mechanism in the initiation of atherosclerosis. A beneficial role of lycopene as antioxidant in the prevention of CVD is suggested but the data are still controversial. Lycopene is believed to be the most potent carotenoid antioxidant in vitro. Tissue culture experiments and animal studies support potential cardioprotective effects for lycopene and other carotenoids in the blood. Most studies showed beneficial effects of lycopene to individuals who are antioxidant-deficient like elderly patients, or humans exposed to higher levels of oxidative stress like smokers, diabetics, hemodialysis patients and acute myocardial infarction patients. By defining the right population and combining antioxidant potentials of lycopene with vitamins and other bioactive plant compounds, the beneficial role of lycopene in CVD can be clarified in future studies.